Compatibility of ZOLL Defibrillators in Simulation-Based Training. Issue 1 (February 2018) - Shoemaker, Jamie Leigh; Duty, Olivia T.; Martin, Kenneth J.; Geis, Gary L.
Abstract : Introduction: In response to the need for high-quality cardiopulmonary resuscitation (CPR) during cardiac arrest, our institution recently purchased ZOLL R Series monitor/defibrillators. This defibrillator provides CPR quality metrics and displays a filtered rhythm through compressions. Purchase of this defibrillator resulted in a practice change and heavily impacted our simulation-based training courses by requiring providers to practice CPR and defibrillation in as close to the real environment as possible. Thus, our objective was to determine which commercial simulators would be compatible with the ZOLL R Series defibrillator system and its CPR feedback functionality in a simulation-based training setting. Methods: Our simulation center uses primarily Gaumard Scientific and Laerdal Medical simulators ranging in size from neonate to adult. Through an iterative process in the laboratory, we evaluated if, and to what level, the CPR display metrics, filtered rhythm, and idle time display could be demonstrated with CPR on the different simulators using infant, pediatric, and adult pads. Results: Certain simulators allow demonstration and real-time practice of defibrillator functions better than others with the ZOLL R Series system when used in the context of CPR training. We have no high-fidelity infant-sized simulators that can meet the depth recommendation for chest compressions given by the American Heart Association. Ventricular fibrillation is the only rhythm that offers a filtered option. Idle time can be reliably displayed for simulators where CPR is detected. Conclusions: When a primary learning objective for simulation-based training involves training on the ZOLL R Series defibrillator, there are a limited number of simulators and rhythms that can accurately represent its features.